2009
DOI: 10.1055/s-0029-1225531
|View full text |Cite
|
Sign up to set email alerts
|

Results of Nasal Screening for Methicillin-ResistantStaphylococcus aureusduring a Neonatal Intensive Care Unit Outbreak

Abstract: Recent reports have implicated community-associated methicillin-resistant Staphylococcus aureus (MRSA) as a cause of outbreaks in the neonatal intensive care unit (NICU). This study was conducted to determine whether community-associated MRSA caused such an outbreak in our NICU and the extent of nasal colonization with MRSA among exposed babies and health care workers. MRSA recovered from infected and colonized babies were genotyped by pulse-field gel electrophoresis (PFGE). Infection control measures were int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
4
0
5
Order By: Relevance
“…[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The studies provided screening data on 19 722 neonatal and pediatric patients. More specifically, 11 studies reported data on 12 284 screened neonates in 12 NICUs, whereas 6 studies reported data on 7107 children hospitalized in 6 PICUs.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The studies provided screening data on 19 722 neonatal and pediatric patients. More specifically, 11 studies reported data on 12 284 screened neonates in 12 NICUs, whereas 6 studies reported data on 7107 children hospitalized in 6 PICUs.…”
Section: Figurementioning
confidence: 99%
“…33 In studies that reported data stratified by year or ICU setting, data sets were split to discrete strata and considered separately. 24,28,34,35,38 The majority of the included studies (11 of 18) were prospective, and the remaining 7 were retrospective.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Hierzu gehört zum Beispiel auch die Rolle des Eintrages von MRGN in die NICU durch besiedelte Eltern [71]. Der von der KRIN-KO bewusst eingeschlagene Weg einer proaktiven Eindämmung der nosokomialen Übertragung aufgrund von Ergebnissen des wöchentlichen Kolonisationsscreenings [12] [12,14,72]. Hierfür ist eine sorgfältige und systematische Beschreibung der beobachteten Ereignisse (am besten im Rahmen prospektiver multizentrischer Studien innerhalb der vorhandenen Netzwerke) von großer Bedeutung.…”
Section: Ausblick Zur Aktuellen Situation In Deutschen Nicusunclassified
“…Carey et al [16] Mongkolrattanothai et al [18] MSSA und MRSA Ja MLVF Murillo et al [19] MRSA Ja PFGE Schlebusch et al [20] MRSA (caMRSA, PVL-positiv, nicht multiresistent) Ja MALDI-TOF, SNP-plus-binary gene typing Song et al [21] MRSA (haMRSA und caMRSA) Ja Rep-PCR Heinrich et al [14] haMRSA (Rhein-Hessen Stamm) Ja PFGE, Phagentypisierung Ali et al [22] MRSA (vorherrschender Ausbruchsstamm: South West Pacific (SWP) Klon, PVL-positiv) Ja PFGE, spa-Typisierung, MLST, MLVA Giuffrè et al [23] MRSA (ST1-MRSA-IVa) Ja MLST, MLVA Köser et al [24] MRSA Ja Gesamtgenomsequenzierung Nübel et al [25] MRSA Ja Gesamtgenomsequenzierung Pinto et al [30] MRSA (PVL-positiv, ST22-MRSA-IV) Ja PFGE, spa-Typisierung, MLST, RLB binary typing Scheithauer et al [15] MRSA Ja PFGE, spa-Typisierung Brennan et al [28] MRSA (PVL-positiv, ST772-MRSA-V) Ja PFGE, DNA microarray profiling und spa-Typisierung, MLST Bei Brennan et al [28] waren 2 Pflegekräfte und 1 Kind (einer Pflegekraft) besiedelt. Eine Pflegekraft, die kürzlich nach Indien gereist war und dort stationär behandelt wurde (Geburt eines Kindes), wurde als "Indexfall" identifiziert.…”
Section: Maßnahmen Der Infektionskontrolleunclassified